Policy and Practice of London's Historic Environment. (3rd April 2019) - Morel, Hana
ABSTRACT: An original approach to understanding London – one of the world's most prominent global cities – and its constant reform and modernisation of governance, planning and the historic environment through the first broad collection of social history. The past 40 to 50 years have seen successive governments attempt to resolve issues of governance, institutional structures and planning. The city, both in government and its institutions, is in a continuous state of flux – like many other global cities – and struggles with shifting boundaries of power as it attempts to strategically govern a range of social, economic, political and environmental challenges. The following paper evidences significant events that have influenced the shaping of planning and archaeology in London, and the organisations and legislation relevant to the practice of London archaeology in a unique way, enriching the basic skeletal history of legal frameworks and changing institutions with historical narratives offered by London archaeologists from a series of 55 in-depth interviews conducted between 2012 and 2013.